Analisis Kompetensi Pedagogik Guru terhadap Proses Pembelajaran Proses Pembelajaran pada Mata Pelajaran Bahasa Inggris di kelas VIII SMPN 35 Medan - Ulfa, Syarifah Widya; Khairani, Rizky Putri Yunisa; Syafira, Syafira; Annisa, Feby (Universitas Muhammadiyah Enrekang, 2024)
In the world of education, the teacher's role is not only limited to providing materials, but also includes the ability to design effective learning, implement teaching strategies that suit student needs, and disseminate learning outcomes. Teacher pedagogical competence is very important in achieving meaningful and effective learning goals. This research aims to analyze the pedagogical competence of English teachers at SMPN 35 Medan, with a focus on learning planning, learning implementation, learning evaluation, and use of learning media. The research method used is descriptive qualitative through interviews and direct observation. It is hoped that the research results will provide a comprehensive picture of the pedagogical competence of English teachers at SMPN 35 Medan and identify areas that require improvement to improve the quality of learning.